ECO_CARE Fieldtrip on the Rio Negro (municipality of Novo Airão, Comunidade Tiririca) and academic collaboration with indigenous women, traditional people and Master’s students - Poto, Margherita Paola; Parola, Giulia (Septentrio Reports, 2024)
This report summarises the activities undertaken by the ECOCARE team during the week of November 3 to November 4, focusing on fieldwork on the Rio Negro, specifically in the municipality of Novo Airão and the Comunidade Tiririca. Additionally, the team organised a meeting with the indigenous women of the Amarn organization and an academic activity on storytelling and emotional literacy with the Master’s students of the Postgraduate Program in Law at the UFAM, emphasizing a hands-on approach to learning and mutual exchange of knowledge. The activities were part of a broader initiative to foster meaningful partnerships and enhance educational opportunities through direct interaction with indigenous communities and academic partners. This initiative aligns with our ongoing commitment to support indigenous scholarship and integrate it within academic frameworks, thereby enriching the educational experiences of all participants.